2019
DOI: 10.1371/journal.pone.0225713
|View full text |Cite
|
Sign up to set email alerts
|

Bone spoons for prehistoric babies: Detection of human teeth marks on the Neolithic artefacts from the site Grad-Starčevo (Serbia)

Abstract: Around 8000 years ago, throughout the Neolithic world a new type of artefact appeared, small spoons masterly made from cattle bone, usually interpreted as tools, due to their intensive traces of use. Contrary to those interpretations, the small dimensions of spoons and presence of intensive traces of use led us to the assumption that they were used for feeding babies. In order to test that assumption we compared 2230 marks on three spoons from the Neolithic site of Grad-Starčevo in Serbia (5800−5450 cal BC) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 61 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…milk and ground cereals) would have provided Neolithic mothers (as well as other members of the community) with novel options for feeding infants and small children prior to introducing solids in their diet. Such baby gruels were possibly served by bone spoons made from cattle metapodial bones, artefacts ubiquitous in the Neolithic Anatolia and the Balkans, as a recent study of bone spoons from the site of Starčevo-Grad has confirmed [108]. These utensils bore numerous traces of use and damage which corresponded to milk teeth marks, likely produced by children during feeding and/or chewing.…”
Section: Plos Onementioning
confidence: 96%
“…milk and ground cereals) would have provided Neolithic mothers (as well as other members of the community) with novel options for feeding infants and small children prior to introducing solids in their diet. Such baby gruels were possibly served by bone spoons made from cattle metapodial bones, artefacts ubiquitous in the Neolithic Anatolia and the Balkans, as a recent study of bone spoons from the site of Starčevo-Grad has confirmed [108]. These utensils bore numerous traces of use and damage which corresponded to milk teeth marks, likely produced by children during feeding and/or chewing.…”
Section: Plos Onementioning
confidence: 96%
“…In analogy with Balkan Neolithic bone spoons, long thought to be a prestigious ritual artefact but recently revealed to have been used in feeding infants (Stefanović et al . 2019), the artefacts perceived as high status or special by archaeologists could, in practice, have been used by a wide range of social actors. While the Cham culture cups have no particular characteristics that would make them especially suitable for use by small children themselves (in contrast to the Bronze Age vessels with spouts discussed in Dunne et al .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been growing recognition of the significance of the mother-infant bond from social and medical perspectives (Brüne and Schiefenhövel, 2019;Kendall et al, 2021), with increasing attention given to understanding the historical and evolutionary aspects of this bond and examining how it has evolved across different periods, regions and cultures (Gowland and Halcrow, 2019;Stefanović et al, 2019;Halcrow et al, 2020;Miller et al, 2020;Rebay-Salisbury and Pany-Kucera, 2020). Taking a broader and long-term view, changes in women's roles and status during motherhood and childcare, including alloparenting, are essential to an in-depth understanding of the evolution of our species (Halcrow et al, 2020).…”
Section: Introductionmentioning
confidence: 99%